Comparison of Alcohol and Cannabis Motives and Context of Use among United Kingdom Students: [Perbandingan Motif dan Konteks Penggunaan Alkohol dan Ganja pada Mahasiswa Britania Raya] - Yuniardi, Muhamad Salis; Rodgers, Jacqueline; Freeston, Mark Henry (Faculty of Psychology, Universitas Surabaya, 2022)
Considerable efforts have been made over a long period of time to understand the variability in substance use and the causal factors underlying it. Therefore, this study aimed to compare motives and the context of alcohol and cannabis use based on a novel measure named the Newcastle Substance Use Questionnaire (NSUQ). Participants were recruited from five universities in the United Kingdom. A total of 58 participants reported using of both alcohol and cannabis during the previous year of the study. Comparisons of motives and context were conducted using General Linear Model - Repeated Measure Analysis of Variance (ANOVA) through International Business Machines Corporation (IBM) Statistical Product and Service Solutions (SPSS) version 21.0. There are differences and similarities regarding motives and contexts of alcohol and cannabis use. “Improving social interaction” was the highest rated on alcohol use, whereas “improving cognitive performance” was the highest rated on cannabis use. Additionally, the most frequent context for both substances is “using with friends”. Bermacam upaya telah dilakukan dalam jangka waktu lama untuk memahami variasi dalam penggunaan zat adiktif dan faktor yang melatarbelakanginya. Studi ini bertujuan membandingkan motif dan konteks penggunaan alkohol dan ganja, dengan menggunakan instrumen pengukuran baru bernama Newcastle Substance Use Questionnaire (NSUQ). Partisipan direkrut dari lima universitas di Britania Raya. Sebanyak 58 partisipan melaporkan penggunaan keduanya dalam setahun terakhir dari waktu pelaksanaan studi ini. Perbandingan motif dan konteks penggunaan dilakukan dengan menggunakan General Linear Model - Repeated Measure Analysis of Variance (ANOVA) pada program International Business Machines Corporation (IBM) Statistical Product and Service Solutions (SPSS) versi 21.0. Ada perbedaan dan persamaan terkait motif dan konteks penggunaan alkohol dan ganja. “Membantu meningkatkan interaksi sosial” adalah motif dengan skor tertinggi terkait penggunaan alkohol, sedangkan “meningkatkan kemampuan kognitif” adalah motif dengan skor tertinggi terkait penggunaan ganja. Selanjutnya, konteks penggunaan yang paling sering terjadi pada penggunaan keduanya adalah “menggunakan bersama teman”.